Conceptual framework: Green leadership enhances green customer citizenship behaviour - George Kofi Amoako; Gifty Agyeiwaa Bonsu; George Oppong Appiagyei Ampong; Antoinette Yaa Benewaa Gabrah; Genevieve Dzigbordi Sedalo (Sustainable Futures)
Businesses are aware of the necessity of incorporating sustainability practices into their business models. This can include things like eco-friendly organizational practices, eco-friendly choice of suppliers, eco-friendly manufacturing processes, eco-friendly production methods, eco-friendly approaches to leadership, and more. These practices if effectively communicated to customers influence their attitudes. Customers that support green consumption will voluntarily recommend and purchase such green products as well as go beyond their role of purchasing to promoting the good image of the brand and company. Nevertheless, there is limited discussion of customer citizenship behaviour in the literature on green marketing. This study therefore explains the interrelationships that exist between green leadership and customer citizenship behaviour. This study is a conceptual in nature. Thus, a non-empirical review of literature. Specifically, the study followed a desk-based research style. Using the triple bottom line theory, the study then proposes that green leadership has a significant impact on firm's green supplier selection, green marketing communication, green organizational practices, green production processes, customer citizenship behaviour and environmentally sustainable procedures. Finally, the research further proposed that green leadership can positively affect green customer citizenship. Therefore, companies must prioritize green leadership to inspire employees to be innovative and creative in developing sustainable manufacturing procedures and products.